Cytogenetic Analysis Of Micronuclei, Sister Chromatid Exchange And Chromosomal Aberrations In Pan Masala Chewers - V. RAMAKRISHNAN; S. GOWTHAM KUMAR; S. GOVINDARAJU (International Journal of Pharma and Bio Sciences, 2011)
Pan Masala (PM) chewing is very dangerous for health but it is becoming very popular day by day. PM is a dried powdered mixture containing ingredients like areca nut, catechu, lime, cardamom and flavouring agents. It is consumed abundantly by Indians and is also exported to Western countries. A cytogenetic study to assess the micronucleus (MN), sister chromatid exchange (SCE) levels and chromosomal aberrations among (CA) 60 pan chewers and 60 non-chewers was conducted in Chennai, Tamil Nadu. In the present cytogenetic monitoring study, analysis of MN was significantly higher (15.82 ± 1.31) in chewers than controls (4.82 ± 1.47) (P < 0.001) and SCE also was significantly higher in chewers (9.23± 2.12) than controls (4.80±1.11) (P < 0.001). In exfoliated buccal mucosa and chromosome analysis (CA), frequency of chromatid type aberrations is lower in controls than chewers such as gaps (0.90% v. 1.83%) breaks (0.47% v. 1.77%), exchanges (0.02% v. 0.18) and acentric fragments (0.20% v. 0.90%). The increased percentage of aberrations found among pan chewers is significantly higher when compared to that of the controls. Isochromatid aberrations also increased significantly such as gaps (0.12% v. 0.97%) breaks (0.07% v. 0.80%), acentric fragments (0.05% v. 0.23%), dicentrics (0.02% v. 0.63%), and these were estimated in the peripheral blood lymphocytes to assess possible DNA damage. All three cytogenetic endpoints demonstrated a statistically significant increase (P < 0.001) among the pan masala chewers as compared with the non-consuming controls. In conclusion, we propose the use of the cytokinesis-block micronucleus assay, sister chromatid exchange and chromosome aberrations for getting a sensitive information on cell cycle progression and cytotoxicity of chewing pan masala.